The role of video games in the development of kindergarten children’s creative thinking skills from the point of view of the instructors - Alamar, Ghadeer Hamad (Journal of Curriculum and Teaching Methodology, 2024)
The purpose of this study is to investigate the impact of video games on the development of creative thinking in kindergarteners from a female instructor’s perspective. The researcher used a descriptive survey approach to survey kindergarten instructors in Hafr Al-Batin Governorate in the second semester of the academic year 2022–2022. One hundred sixty-nine female instructors were involved. The respondents acknowledged that video games are becoming more important in encouraging creative thinking in kindergarteners. Flexibility skills were the most important, followed by attention to detail, fluency, and originality skills. Video games encourage children to initiate with excitement and fun, stimulate their imaginations, and help them recall prior experiences to quickly discover solutions. There were no other statistically notable disparities between the study sample’s average responses to analyze the effect of video games in developing kindergarteners’ creative thinking based on age, specialization, form of kindergarten, and years of experience. A number of recommendations followed the findings, notably that the Ministry of Education should strengthen the kindergarten stage by working with private companies to produce acceptable video games, integrating them into the curriculum. The researcher proposed research on the impact of video games on creative thinking skills at various academic levels.